Communicating with patients, families and health professionals about managing medications in intensive care: A qualitative observational study. (October 2019) - Manias, Elizabeth; Braaf, Sandy; Rixon, Sascha; Williams, Allison; Liew, Danny; Blackburn, Aleesha
Abstract: Objectives: To explore communication between patients, families, and health professionals about managing medications in intensive care. Design: A qualitative exploratory study was undertaken using participant observations. A thematic analysis of the data was performed. Setting: The setting comprised an intensive care unit at a public, teaching hospital in Melbourne, Australia. Findings: Three themes were identified: provision of information, therapeutic relationships, and patient and family centred care . Nurses and pharmacists communicated regularly about medications with patients and family members. Doctors were occasionally present at the bedside during medical ward rounds or in undertaking medical procedures and subsequently their patient and family interactions about managing medications tended to be minimal. Pharmacists spent time in clarifying patients' medication history prior to their admission to the intensive care unit. Nurses were at the forefront of communication with patients and their family members. However, nurses sometimes missed cues and valuable opportunities to respond to families' concerns during their interactions. Communication was commonly hampered by time constraints and competing responsibilities of health professionals. Conclusion: Communication tended to involve clarification of patients' medication history and the ways in which medications affected patients' clinical status or medical condition. Attention is needed in attending to cues from families in communicating about medications.